2022
DOI: 10.1002/cctc.202200135
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 5‐Hydroxymethyl Furfural to 2,5‐Furan Dicarboxylic Acid Under Mild Aqueous Conditions Catalysed by MIL‐100(Fe) Metal‐Organic Framework

Abstract: We present the use of the redox active MIL-100(Fe) metalorganic framework (MOF) as a catalyst for the oxidation of 5hydroxymethyl furfural (HMF) into 2,5-furan dicarboxylic acid (FDCA) in water. The MOF is synthesised in water alone under mild hydrothermal conditions and 1 H NMR is used to analyse the products of HMF oxidation. The MOF in combination with the co-catalyst TEMPO provides a total selectivity of desired products of 74 % with a maximum FDCA yield of 57 % seen after 24 hours at only 70 °C. The catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…[30][31][32][33][34][35][36] During recent years, metal-organic frameworks (MOFs) have been regarded as one of the most popular and useful catalysts for laboratory and commercial scale organic synthesis. [37][38][39][40][41][42][43][44][45][46][47] On the ecological side, MOFs have been known as the low-cost and green solid supports, applied to immobilize the soluble catalysts due to their crucial role in lowering the toxicity, having heterogeneous 48,49 high specic surface area, possessing porous nature and also structural diversity, being economically viable and also having safe and recyclable characteristics to synthesize organic moleculesleading to the synthesis of a wide variety of MOF catalysts, 50,51 i.e. MIL-53 (Fe) which is an Fe-based MOF with high thermal stability and a very high surface area.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] During recent years, metal-organic frameworks (MOFs) have been regarded as one of the most popular and useful catalysts for laboratory and commercial scale organic synthesis. [37][38][39][40][41][42][43][44][45][46][47] On the ecological side, MOFs have been known as the low-cost and green solid supports, applied to immobilize the soluble catalysts due to their crucial role in lowering the toxicity, having heterogeneous 48,49 high specic surface area, possessing porous nature and also structural diversity, being economically viable and also having safe and recyclable characteristics to synthesize organic moleculesleading to the synthesis of a wide variety of MOF catalysts, 50,51 i.e. MIL-53 (Fe) which is an Fe-based MOF with high thermal stability and a very high surface area.…”
Section: Introductionmentioning
confidence: 99%
“…A-H and L-H had some identical peaks, including 2.67, 4.63, and 9.58 ppm, which were derived from the ring-opening intermediate DHH . The difference was that the peaks at 6.61 and 7.50 ppm in A-H came from residual HMF, while the peaks at 6.61 and 7.50 ppm in L-H demonstrated that L-H contained not only HMF but also HKPA . The 1 H NMR spectrum of HKPA is inserted in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…43 The difference was that the peaks at 6.61 and 7.50 ppm in A-H came from residual HMF, while the peaks at 6.61 and 7.50 ppm in L-H demonstrated that L-H contained not only HMF but also HKPA. 45 The 1 H NMR spectrum of HKPA is inserted in Figure 3c. HMF could be oxidized by singlet-oxygen ( 1 O 2 ) under visible light, affording the ringopening product HKPA.…”
Section: Structural Characterization Of L-h and A-hmentioning
confidence: 99%
“…[8,9] Almost quantitative yields to FDCA have been achieved over supported noble-metal (Au, Ru, Pd, Pt) nanoparticles as catalysts under relatively mild conditions in the presence of an alkaline medium. [10][11][12][13][14] Intensive research has been devoted to gain advanced insights on the reaction mechanism and to disclose the role of metal phase, [9,13,[15][16][17][18][19][20][21] particle sizes, [22] support chemistry [19,[23][24][25][26][27][28][29] and promoter addition [14,30,31] with the aim to optimize catalyst formulation and process conditions, with particular emphasis to the adoption of base-free conditions. [16,[32][33][34][35][36] Nevertheless, the large scale production of FDCA under environmentally benign conditions and its use as monomer for PEF synthesis is still hindered by some drawbacks associated with the large polarity, high boiling point, poor solubility of FDCA together with its tendency to undergo decomposition during the polymerization procedure, which results in a PEF product with undesirable color.…”
Section: Introductionmentioning
confidence: 99%